TEACHING LANGUAGE THROUGH LITERATURE - Vineet Kaul (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2013)
While literature-based instruction has been highly praised for its pedagogical benefits, it on fronts entrenched learning hindrances, both linguistic and cultural in EFL settings. Whether the literature instruction in practice is motivating or demotivating is an issue worthy of concern. In this article the writer surveys attitudes to the integration of language and literature teaching, noting the reservations that have been expressed about it in the past, and which still continue to linger in some quarters..This paper interrogates the role of literature in the language classroom, communicative approaches and emphasis on practical functions of English language. During the 1980`s there was a comeback of interest in literature and language teaching. Linguistics and other contributors suggested that literature should be involved in classes of English for non-native learners but in another pedagogical approach…”the teaching of literature is an arid business unless there is a response, and even negative responses can create an interesting classroom situation”(Long, 1987). The revival of literature is characterized as “literature wearing different clothing.” What kind of literature to use? Texts should be chosen according to students' needs, interests, cultural background, and language level. Selected books must be relevant to the life experiences, emotions, or dreams of learners. This paper suggests choosing a work that is not much above the student's reading proficiency." Interest, appeal, and relevance are all more important." Keywords: language, literature, pedagogical approaches, non-native learners.